EFEKTIFITAS TERAPI AKUPRESUR TITIK BL 23 UNTUK MENGURANGI NYERI PINGGANG PADA IBU HAMIL TRIMESTER III - Sari, Intan Widya; Yulviana, Rina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Back pain can cause fatigue both physically and emotionally, and interfere with daily activities in pregnant women. Efforts to overcome complaints of back pain in pregnant women are carried out with acupressure at the Bladder 23 point (BL 23). The purpose of this study was to determine the effectiveness of acupressure therapy at the Bl 23 point in reducing back pain in pregnant women in the third trimester. The research location was at the Anaku Kamiyu Mom and Baby Spa Clinic. The population in this study was 31 pregnant women in the third trimester. The sample in this study was 17 people with inclusion and exclusion criteria. Data analysis used univariate and bivariate. The univariate results, before being given BL23 acupressure, the majority of 15 respondents (98.0%) had pain intensity in the range of 7–10 with the category of severe pain, while a minority of 2 respondents (2.0%) had pain intensity in the range of 4–6 with the category of moderate pain. Meanwhile, after being given BL23 acupressure, the majority of 16 respondents (99.0%) had pain intensity in the range of 4–6 with a moderate pain category, while a minority of 1 respondent (1.0%) had pain intensity in the range of 7–10 with a severe pain category. Bivariate results using the Wilcoxon test with results on the back pain variable with a p-value = 0.000 (<0.05). In conclusion, acupressure at the BL23 point is effective in reducing back pain in pregnant women in their third trimester. It is hoped that respondents will undergo BL23 acupressure therapy. It is hoped that the Anaku Kamiyu Mom and Baby Spa Clinic can utilize leaflets as an educational tool for pregnant women in their third trimester about the benefits of acupressure therapy at the BL23 point in reducing back pain.Keywords: Acupresure, Therapy BL 23; Pregnant Women in Third Trimester